Novel loss-of-function mutation in HERC2 is associated with severe developmental delay and paediatric lethality. Issue 5 (22nd June 2020) - Elpidorou, Marilena; Best, Sunayna; Poulter, James A; Hartill, Verity; Hobson, Emma; Sheridan, Eamonn; Johnson, Colin A
Abstract : Background: The HERC2 gene encodes a 527 kDa E3 ubiquitin protein ligase that has key roles in cell cycle regulation, spindle formation during mitosis, mitochondrial functions and DNA damage responses. It has essential roles during embryonic development, particularly for neuronal and muscular functions. To date, missense mutations in HERC2 have been associated with an autosomal recessive neurodevelopmental disorder with some phenotypical similarities to Angelman syndrome, and a homozygous deletion spanning HERC2 and OCA2 causing a more severe neurodevelopmental phenotype. Methods and results: We ascertained a consanguineous family with a presumed autosomal recessive severe neurodevelopmental disorder that leads to paediatric lethality. In affected individuals, we identified a homozygous HERC2 frameshift variant that results in a premature stop codon and complete loss of HERC2 protein. Functional characterisation of this variant in fibroblasts, from one living affected individual, revealed impaired mitochondrial network and function as well as disrupted levels of known interacting proteins such as XPA. Conclusion: This study extends the genotype–phenotype correlation for HERC2 variants to include a distinct lethal neurodevelopmental disorder, highlighting the importance of further characterisation for HERC2 -related disorders.